Ano-rectal Melanoma: A Rare Case Report - Khatoon, Ayesha; Vasantham, Vyshnavi; Sharma, Urvashi; Yadav, Shakti Kumar; Kalra, Rupinder; Jahan, Aarzoo; Singh, Sompal; Sarin, Namrata; Pruthi, Sonam Kumar (Annals of Pathology and Laboratory Medicine, 2020)
Ano-rectal melanoma is extremely rare and has dismal prognosis when compared to cutaneous melanomas. It presents as ano-rectal mass and patients usually complain of passing blood in stools. Being, a highly aggressive neoplasm, widespread metastasis is common, which can be seen even at the time of diagnosis. Here, we present a case report of ano-rectal melanoma in a 40-year old male, who presented with complaints of anal growth since one month. Initially, a clinical diagnosis of rectal carcinoma was suspected. However, biopsy of the growth showed histomorphological features of melanoma, which were confirmed on immunohistochemistry.